The investigation of variables predicting the situation of drug addiction in the families of university students - Tanhan, Fuat; Mukba, Gamze (Journal of Dependence, 2014)
Objective: Children of alcoholic parents tend to behave erratically in interpersonal relationships that are associated with a variety of physical, psychological and behavioral disorders including codependency, low self-esteem, depression, anxiety, allergy, social closeness, asthma, having difficulties to express feelings in their advanced lives. Those variables based upon the substance dependency of the family, can be thought as the predictorvariablesofalcohol orsubstance abuse. The variables such as low selfesteem, codependency, social withdrawal, inability to reflect feelings, anxiety and depression that are associated with alcohol or drug addiction can be observed in Turkey. In this study, it has been aimed to determine the predictor variables affecting the families of university students which have alcohol or drug addicted members.Method: The Spann-Fischer Codependency Scale-SFCDS, General Health Questionnaire-GHQ-12, Rosenberg Self Esteem Scale-RSES, the Emotion awareness (EA) subscale of Dimension of Interpersonal Relationship Scale and individual information form have been used. In the analyzing of the data, Binary Logistic Regression Analysis method has been used.Results: According to the results of this research, “domestic violence” was found as a significant predictor on being the member of non-addicted family to alcohol or substance (p
Keywords: Alcohol or drug addiction; predictor variable